Relationships Between Ion Channels, Mitochondrial Functions and Inflammation in Human Aging - Strickland, Marie; Yacoubi-Loueslati, Besma; Bouhaouala-Zahar, Balkiss; Pender, Sylvia L. F.; Larbi, Anis (Frontiers in Physiology, 2019)
Aging is often associated with a loss of function. We believe aging to be more an adaptation to the various, and often continuous, stressors encountered during life in order to maintain overall functionality of the systems. The maladaptation of a system during aging may increase the susceptibility to diseases. There are basic cellular functions that may influence and/or are influenced by aging. Mitochondrial function is amongst these. Their presence in almost all cell types makes of these valuable targets for interventions to slow down or even reserve signs of aging. In this review, the role of mitochondria and essential physiological regulators of mitochondria and cellular functions, ion channels, will be discussed in the context of human aging. The origins of inflamm-aging, associated with poor clinical outcomes, will be linked to mitochondria and ion channel biology.